The efficacy and safety of the prophylactic application of PEG-rhG-CSF in radiotherapy with weekly concurrent chemotherapy for cervical cancer - Huimin Chen; Yiming Ma; Dandan Wang; Hao Wu; Mingchuan Zhang; Yuanyuan Xu; Shuxia Cheng (BMC Cancer)
Abstract Objective To evaluate the efficacy and safety of pegylated recombinant human granulocyte colony stimulating factor (PEG-rhG-CSF) in preventing neutropenia during concurrent radiotherapy combined with weekly chemotherapy in patients with cervical cancer. Methods From September 2019 to November 2020, 180 patients with cervical cancer who required concurrent chemoradiotherapy (CCRT) were enrolled in this study. The patients were randomly divided into the following three groups at a ratio of 1:1:1: Group A (PEG-rhG-CSF), Group B (PEG-rhG-CSF + rhG-CSF) and the control group (rhG-CSF). Cisplatin or carboplatin was administered weekly. The primary endpoint was the incidence of grade 3/4 neutropenia. The secondary endpoints were the incidence of febrile neutropenia (FN), delay of radiotherapy, chemotherapy dose reduction, rate of PFS at 2 years and 3 years, and incidence of adverse reactions. Results Sixty patients were randomly assigned to each group. Two patients in Group B withdrew from the trial for personal reasons. The incidence of grade 1/2 neutropenia in the Control group was significantly lower than that in Group A and Group B (P < 0.001). However, the incidence of grade 3/4 neutropenia in the Control group was significantly greater than that in Group A and Group B (P < 0.001). There was no significant difference in the incidence of FN among the three groups (P = 0.771). The rate of platinum dose reduction in Group A (6.7%) and Group B (5.2%) was significantly lower than that in the Control group (30.0%) (P < 0.001). The delay rate of radiotherapy in Group A (10%) and Group B (13.8%) was obviously inferior to that in the Control group (31.7%) (P = 0.006). The 2-year PFS rates of Group A, Group B, and the Control group were 93.3%, 98.3%, and 91.7%, respectively, with no statistically significant difference (P = 0.270). The 3-year PFS rates were 89.8%, 94.1%, and 84.9%, respectively, with no statistically significant difference (P = 0.178). No treatment-related serious adverse events occurred in any of the patients. Conclusion In Group A and Group B, The prophylactic application of PEG-rhG-CSF during conventional chemoradiotherapy combined with weekly chemotherapy for patients with cervical cancer can reduce the incidence of grade 3/4 neutropenia and does not increase the incidence of adverse reactions when compared to Control group. Trial registration chictr.org.cn, ChiCTR1900026309, registered 29 September 2019-prospectively registered.